Faktor-Faktor yang Mempengaruhi Pengelolaan Keuangan Usaha Kecil Menengah dan Implikasinya terhadap Good Governance - Pituringsih, Endar; Asmony, Thatok; Basuki, Prayitno (E-Jurnal Akuntansi, 2020)
The study aims to obtain empirical evidence about the influence of organizational commitment, accounting information systems and human resource capacity on Small Medium Enterprise (SME) financial management and the influence of SME financial management on good governance. The study was conducted on SMEs in West Lombok Regency.  various regions in West Lombok Regency The results of the study indicate that organizational commitment does not significantly influence financial management Information technology and HR competencies significantly influence financial management and financial management significantly influence good governance. Keywords: Commitment; Competent; Technology; Financial Management; Good Governance.